The stability of human, bovine and avian tuberculin purified protein derivative (PPD) - Maes, Mailis; Giménez, José Francisco; D’Alessandro, Adriana; de Waard, Jacobus H. (The Journal of Infection in Developing Countries, 2011)
Introduction: Guidelines recommend storing tuberculin purified protein derivative (PPD) refrigerated. However, especially in developing countries, maintaining the product refrigerated under field conditions can be difficult, limiting its use. Here we determine the effect of prolonged exposure to high temperatures on the potency of human, bovine and avian tuberculin PPD. Methodology: Human, bovine and avian tuberculin PPD were stored for several weeks exposed to temperatures ranging from 37º to 100ºC. The potency was evaluated in vivo, in sensitized or naturally infected animals. Results: Most test situations didn't affect the biological activity of the tuberculin PPDs and only very long and extreme incubations (several days at 100°C) compromised the potency. Conclusions: Tuberculin PPD is very stable and can be stored or transported for long periods without refrigeration.